Pengaruh Faktor Psikologis : Kecemasan Terhadap Kunjungan Antenatal Care di Puskesmas Mandala Lebak Banten Tahun 2025 - Elfira Sri Futriani; Shella Sulistiatun Nisa (Universitas Pahlawan Tuanku Tambusai, 2025)
Pregnant women experience psychological changes which are influenced by an increase in the hormone progesterone and personality factors. Pregnant women who accept pregnancy find it easier to adjust, while pregnant women who do not accept pregnancy can experience psychological disorders and emotional instability. Purpose of writing: To determine the influence of psychological factors: anxiety on antenatal care visits at the Mandala Lebak Banten Community Health Center. This research uses a quantitative descriptive research type with a cross sectional study approach, the sample in this research was 40 pregnant women, chi square statistical analysis test. There is an influence of psychological factors: anxiety on antenatal care visits with a value of p=0.000. carry out comprehensive antenatal care examinations by offering psychological support to pregnant women who experience disorders such as anxiety and referring to professionals if necessary.